Influence of Child Abuse on Youth Restiveness as Perceived by Security Personnel in Ilorin Metropolis, Kwara State - Okesina, Falilat Anike (Jurnal Kajian Bimbingan dan Konseling, 2025)
The rate at which Nigerian youths take up arms to perpetuate anti-social acts has become a major concern to the populace. This study investigated the influence of child abuse on youth restiveness as perceived by security personnel in Ilorin metropolis, Kwara State. The study was a survey research. The population of this study comprised all security personnel in Ilorin metropolis and 200 respondents were randomly selected for the study. A questionnaire entitled “Influence of Child Abuse on Youths Restiveness Questionnaire” (ICAYRQ) was used to collect data for the study. Percentage was used to analyse the demographic data. Mean and rank order analysis was used to answer the research question while the four null hypotheses formulated were tested using t-test and ANOVA statistical techniques. The findings of the study revealed that security personnel attested that child abuse on youth has a negative influence on the youth’s restiveness and it made victims exhibit antisocial behaviour and delinquency; lack empathy and compassion towards others; and exhibit aggressive behaviour towards others. The study further revealed that there was no significant difference in the influence of child abuse on youth restiveness as perceived by security personnel in Ilorin metropolis based on gender, age, educational qualification and years of experience. Based on the findings of this study, it was recommended that security agencies should establish and strengthen support services such as counselling and therapy for victims of child abuse. Counsellors should work closely with security personnel to ensure a coordinated approach to addressing youth restiveness.